Spatial Variations in Inflation Dynamics: A Comparative Analysis of Food and General Consumer Price Indices Across Nigerian States (January 2023–January 2024) - Ayenigba, Alfred Ayo; Ajao, Olutunde Michael; Igbobie, Emeka Joseph (Darul Yasin Al Sys, 2025)
This study investigates spatial variations in inflation dynamics across Nigerian states between January 2023 and January 2024, with emphasis on food and general Consumer Price Indices (CPI). Drawing on data from the National Bureau of Statistics, the analysis applies descriptive statistics, Kruskal–Wallis tests, and Moran’s I spatial techniques to uncover regional disparities. Results indicate that food inflation (30.65%) consistently exceeded general inflation (25.88%), with states such as Kogi and Imo experiencing the widest gaps, largely attributable to supply chain inefficiencies and agricultural disruptions. Spatial clustering revealed distinct inflationary patterns, with high-inflation zones concentrated in the South-East and relatively lower inflation in the North-East, influenced by insecurity and infrastructure deficits. These findings underscore the need for region-specific policy measures that address structural drivers of inflation, particularly through targeted interventions in food security, supply chain resilience, and infrastructure development, in order to mitigate inflation’s socioeconomic impacts and promote economic stability.